Studi Literatur: Potensi Buah Merah (Pandanus Conoideus) Sebagai Agen Hipolipidemik Dalam Menurunkan Kolesterol - Fransina Revalina (Bajang Institute, 2026)
Hypercholesterolemia is a condition characterized by elevated blood cholesterol levels and is a major risk factor for the development of cardiovascular diseases. Long-term use of cholesterol-lowering drugs may cause adverse effects, highlighting the need for alternative therapies derived from natural products. Red fruit (Pandanus conoideus Lam.), an endemic plant from Papua, Indonesia, contains various bioactive compounds, including β-carotene, tocopherols, flavonoids, and unsaturated fatty acids, which are believed to contribute to improving lipid profiles. This study aimed to review the potential of red fruit as a hypolipidemic agent based on published scientific evidence. The study employed a literature review method by analyzing scientific articles obtained from various reputable databases. The findings indicate that the administration of red fruit extract, oil, and filtrate significantly reduced total cholesterol, low-density lipoprotein (LDL), and triglyceride levels while increasing high-density lipoprotein (HDL) levels. These hypolipidemic effects are associated with the antioxidant properties of red fruit and the ability of its bioactive compounds to regulate lipid metabolism. Based on the reviewed evidence, red fruit demonstrates considerable potential as a natural hypolipidemic agent for supporting the management of hypercholesterolemia